Immunohistochemical Investigation of TNF-a Expression in Sheep and Goat Lung Paraffin Blocks Infected with Natural Respiratory Syncytial Virus (RSV) - TERZİ, Funda; ULUSOY, Yavuz; KILINÇ, Bahadır; DAL, Ayşe Gül; SALİK, Rabi (Uludag Universitesi Veteriner Fakultesi Dergisi, 2022)
Respiratory Syncytial Virus (RSV) is an important cause of sheep and goat respiratory tract disease. RSV usually replicates in the airway epithelium and proinflammatory cytokines and chemokines are induced. In this study, it was aimed to investigate TNF-a expression in natural RSV-infected sheep and goat lung paraffin blocks by immunohistochemical method. The study material consisted of twenty nine lung archive paraffin blocks (nineteen sheep and ten goats), which were admitted to Etlik Veterinary Control and Research Institute from Ankara and surrounding provinces with the suspicion of pneumonia between 2015 and 2020. Histopathological findings such as degeneration and desquamation in the bronchi and bronchial epithelium, fibromuscular hypertrophy, hyperplasia in the peribronchial lymphoid tissue, cell infiltration in the interalveolar septum, and no statistical difference was detected in the sheep and goat lung paraffin block tissues (p> 0.05). Immunohistochemically, RSV replication in bronchial and bronchial epithelium and cell debris, bronchial glands, interalveolar septum inflammatory cells, alveolar macrophages was statistically similar in sheep and goats (p> 0.05). It was determined that the expression of TNF-a was more intensely stained in the lung tissue of goats than sheep (p
Keywords: Veterinary Surgery; Veteriner Cerrahi; RSV; TNF-a; Immunohistochemistry; Sheep; Goat; RSV; TNF-a; İmmunohistokimya; Koyun; Keçi; 2. Zero hunger; 3. Good health